Comparing therapeutic‐focused ultrasound (TFUS) in conjunction with bosutinib versus independent TFUS administration among Alzheimer's patients. (31st December 2021) - Habelhah, Barshen; Mahdavi, Kennedy D; Zielinski, Margaret A; Haroon, Jonathan; Kuhn, Taylor P; Becerra, Sergio A; Barrows, Hannah R; Evans, Natalie E; Spivak, Norman; Whitney, Michael; Mamoun, Michael S; Bystritsky, Alexander; et al.
Abstract: Background: To date, there are limited therapeutic options for the treatment or symptomatic relief of degenerative dementia [1]. There has been growing interest in the class of medications known as tyrosine kinase inhibitors, such as bosutinib, as a therapeutic intervention for dementia [2]. Ongoing clinical and preclinical trials also suggest focused ultrasound may yield therapeutic potential for patients with neurodegenerative conditions such as Alzheimer's disease [3‐5]. Focused ultrasound may be used as an independent therapeutic intervention or adjunctively to facilitate delivery of medicine. The present study compares the efficacy of focused ultrasound as an independent intervention to the efficacy of focused ultrasound combined with bosutinib, using several outcome measures to demonstrate accuracy. Methods: Structural and functional imaging were used to navigate cerebral and subcortical ultrasound targets for 13 patients (9 female; M age = 72.08 years, SD age = 9.30 years), 7 of which received therapeutic ultrasound as an independent intervention, and the remaining 6 received both therapeutic ultrasound in conjunction with bosutinib. The Clinical Dementia Rating scale (as estimated by the Quick Dementia Rating System [QDRS]) was the primary cognitive status outcome measure. Secondary outcome measures included the Montreal Cognitive Assessment [MoCA]. Results: The combination of therapeutic ultrasound with bosutinib was associated with 66% of patients maintaining or improving their Clinical Dementia Rating scale during the eight‐week protocol, whereas therapeutic ultrasound as a stand alone intervention showed 43% of patients maintaining or improving their Clinical Dementia Rating scale. Similarly, 67% of patients who underwent the combination intervention maintained or improved their MoCA scores, and of the patients who only received therapeutic ultrasound, 57% maintained or improved their MoCA scores. Conclusions: The results of these comparisons suggest a combination of medication and therapeutic ultrasound may have a more positive outcome than therapeutic ultrasound alone. Clinical studies have shown that this ultrasound technology has been successfully applied for small molecules [6]. This technique of tailored targeting for each patient's brain in conjunction with medication may represent a significant advancement to the field. Future studies should explore this combination.